Origins of major and minor ash constituents of solid recovered fuel for co-processing in the cement industry. (1st May 2021) - Viczek, S.A.; Aldrian, A.; Pomberger, R.; Sarc, R.
Highlights: Origins of Al, Ca, Fe, Si, Ti, Mg, S, Na, K, and P are discussed using literature. Ash contents and compositions of sorted SRF fractions are determined. Contributions of material fractions to the recyclable share of SRF is investigated. The main SRF fraction recycled in the cement kiln is the fine fraction. The cement industry therefore offers a way to complement conventional recycling. Abstract: Solid recovered fuel (SRF) ash consists of element oxides, which are valuable materials for cement manufacturers. When SRF is co-processed in the cement industry, its mineral content is incorporated into the clinker. Therefore, from a technical perspective, SRF ash is recycled. However, since recycling processes for materials that may be present in SRF exist, and since recycling goals are defined for different waste types, understanding the origin of these ash constituents and the contribution of different materials to the Recycling-index (R-index, i.e., the material-recyclable share of SRF) is important. In this work, the origins of Al, Ca, Fe, Si, Ti, Mg, Na, K, S, and P were first reviewed. Subsequently, ten SRF samples were sorted, and the ash content and composition of the sorting fractions (e.g., <10 mm, plastics, paper&cardboard) determined. Additionally, selected samples of polyethylene (PE), polypropylene (PP), polystyrene (PS), polyethylene terephthalate (PET), polyvinyl chloride (PVC), liquid packaging board (LPB), wood, and paper&cardboard (P&C) extracted from SRF were investigated. The results demonstrated that the materials that contributed most of the valuable oxides and ash content, and thereby to the R-index of SRF, are mixed or composite fractions, for example, the fine fraction, composites, and the sorting residues. Except for the composite LPB, no other material recovery options exist for most of these fractions. For this reason, the recycling of mixed and soiled materials or residues in the cement industry may be considered a complementary option to existing recycling processes.